Akibat Hukum Pencatatan Perkawinan Beda Agama - Mardalena Hanifah (UIR Press, 2023)
Marriage is a legal contract between two individuals who are bound by law and religion to build a happy household for the rest of their lives. Every couple marries for love and the desire to live together legally and officially. Marriage is also essential in religion since it is viewed as a holy connection that God blesses. The legal ramifications of recording marriages of different religions are the focus of this study. The purpose of this research is to examine the legal implications of recording marriages between people of various religions. This study is normative, employing an approach to legal concepts in Marriage Act No. 1 of 1974. According to the research, interfaith marriage is outlawed and ruled religiously unlawful under Indonesian law, but its registration is valid under state law. As a legal result of the existence of marriage registration, the marriage's status is valid, therefore the bond between husband and wife who give birth to children through interfaith marriage provides the kid with legal standing and is legally recognized.